Identification of Open Stomata1-Interacting Proteins Reveals Interactions with Sucrose Non-fermenting1-Related Protein Kinases2 and with Type 2A Protein Phosphatases That Function in Abscisic Acid Responses . Issue 1 (14th July 2015) - Waadt, Rainer; Manalansan, Bianca; Rauniyar, Navin; Munemasa, Shintaro; Booker, Matthew A.; Brandt, Benjamin; Waadt, Christian; Nusinow, Dmitri A.; Kay, Steve A.; Kunz, Hans-Henning; Schumacher, Karin; DeLong, Alison; et al.
Abstract : Abscisic acid-activated protein kinases interact with each other and with protein phosphatases that modulate abscisic acid responses. Abstract: The plant hormone abscisic acid (ABA ) controls growth and development and regulates plant water status through an established signaling pathway. In the presence of ABA, pyrabactin resistance/regulatory component of ABA receptor proteins inhibit type 2C protein phosphatases (PP2Cs). This, in turn, enables the activation of Sucrose Nonfermenting1-Related Protein Kinases2 (SnRK2). Open Stomata1 (OST1)/SnRK2.6/SRK2E is a major SnRK2-type protein kinase responsible for mediating ABA responses. Arabidopsis ( Arabidopsis thaliana ) expressing an epitope-tagged OST1 in the recessive ost1-3 mutant background was used for the copurification and identification of OST1-interacting proteins after osmotic stress and ABA treatments. These analyses, which were confirmed using bimolecular fluorescence complementation and coimmunoprecipitation, unexpectedly revealed homo- and heteromerization of OST1 with SnRK2.2, SnRK2.3, OST1, and SnRK2.8. Furthermore, several OST1-complexed proteins were identified as type 2A protein phosphatase (PP2A) subunits and as proteins involved in lipid and galactolipid metabolism. More detailed analyses suggested an interaction network between ABA -activated SnRK2-type protein kinases and several PP2A-type protein phosphatase regulatory subunits. pp2a double mutants exhibited a reduced sensitivity to ABA during seed germination and stomatal closure and an enhanced ABA sensitivity in root growth regulation. These analyses add PP2A-type protein phosphatases as another class of protein phosphatases to the interaction network of SnRK2-type protein kinases.